Canada's National Advisory Committee on Immunization: Celebrating 50 Years. Issue 3 (2015) - Desai, Shalini; lsmail, Shainoor J; Lerch, Robert; Warshawsky, Bryna F; Gemmill, Ian
Abstract : Vaccines have saved more lives than any other innovation in modern medicine. National immunization committees play a vital role in the development of evidence-based recommendations for the use of vaccines. The present article describes the evolution and work of the National Advisory Committee on Immunization in Canada as the group marks its 50th anniversary. The article also provides insight into the future challenges that the committee is likely to face.